Transformasi Dalam Tradisi Bai’at Gadang Tarekat Syatariah Di Ponpes Nurul Yaqin Ringan-ringan - Pratama, Yoga; Sukri, Alvi (TAMADDUN, 2023)
Bai'at Gadang is a tradition in the sharia congregation that involves spiritual initiation and commitment of its participants to follow the teachings of the congregation. This study aims to explore more broadly the tradition of the Bai'at Gadang Tarekat Syariah and see the transformation that occurred in the implementation procedures, meaning and participants in the event held at the Nurul Yaqin Light-ringan Islamic Boarding School. Through a qualitative approach and data collection through interviews, participant observation, and document analysis, this research reveals important aspects of the Bai'at Gadang tradition. The findings of this study also reveal that bai'at gadang is a derivative practice of bai'at which is usually carried out among followers of the sharia tarekat. In its development, the practice of bai'at gadang underwent transformation in three forms: first, changes in implementation procedures such as time, place and management. Second, changes in the number of participants. Third,change in form of meaning. This study provides in-depth insight into religious practices and spirituality in the context of Islamic boarding schools in Padang Pariaman Regency. This research can also be used as a basis for developing further understanding of the sharia congregation and the Bai'at Gadang tradition among academics, religious observers and religious practitioners.